Pandemic (COVID‐19) Policy, Regional Cooperation and the Emerging Global Production Network†. Issue 1 (9th June 2020) - Kimura, Fukunari; Thangavelu, Shandre Mugan; Narjoko, Dionisius; Findlay, Christopher
Abstract : In this paper, we explore the possible policy responses to the COVID‐19 pandemic shock as well as the related economic (financial crisis) shocks on trade and global value chains (GVC) in East Asia. We find that regional policy coordination is critical to mitigate and isolate the pandemic shock. It is important to identify the pandemic events early to flatten the pandemic curve at the national and regional level. This supports a recent study by the World Bank (2020), which highlights the importance of early mitigation policies during the pandemic shock. The cost of the pandemic and economic shocks will increase significantly when several countries in the region experience the pandemic shock concurrently. In this case, flattening the regional pandemic curve becomes important. The results also indicate the need for greater coordination in East Asia to mitigate the pending economic shock in terms of unemployment, corporate bankruptcy and financial market fragility. The paper also highlights that the stability of the GVC network is critical during the pandemic in terms of hedging the risk of disruptions to the procurement of critical medical and health products as well as maintaining service linkages to manufacturing, such as the logistics sector. Regional policy coordination and the stability of GVC will be valuable in the post‐pandemic recovery of the region.